Development And Validation Of Stability Indicating Hptlc Method For Simultaneous Estimation Of Azithromycin, Fluconazole And Ornidazole In Combined Dosage Form - Solat, Sarla Sakharam; Sharma, Neeraj; Bairagee, Deepika; Pardhe, Ayodhya Tanhaji; Chundawat, Rituraj Singh; Rathore, Udai Bhan Singh (Journal of Neonatal Surgery, 2025)
For the simultaneous quantitative determination of azithromycin (AZM), fluconazole (FLZ), and ornedizole (OZ) in tablet Combi-kit quantities, a quick, reliable, and high-performance thin-layer chromatography (HPTLC) method was developed and tested. HPTLC silica gel 60 F254 plates comprised the stationary phase, and a mixture of toluene, methanol, and 1,4-dioxane in a volume ratio of 2:2:6 made up the mobile phase. A CAMAG TLC Scanner 3 was used to conduct densitometric scanning at a wavelength of 210 nm. The International Council for Harmonization's standards were used to validate the procedure. The RF values for AZM, FLZ, and OZ were 0.202, 0.382, and 0.522, respectively. In this instance, the statistical tests for assessing the appropriateness of the simple linear regression model that were previously described are used to our models AZM (y = 4.506x + 2189.4), FLZ (y = 4.506x + 2189.4), and OZ (y = 4.8969x + 240.53). LOD= 3s/S and LOQ = 10s/S (2) where s is the standard deviation of y-intercept and S is the slope of the calibration curve. The LOD and LOQ were found to be 0.0467and 0.141 g/zone, respectively. Using these methods, it is possible to routinely analyze these three medications in their pharmaceutical dosage form. For several parameters, the results for both analytical methods were tested and validated in accordance with ICH recommendations